A Study of the Concept of Death in Mary Oliver’s Selected Poems in the Light of George Bataille’s Theory of General Economy - Ali Jamali (Critical Literary Studies)
The American ecopoet, Mary Oliver (1935 – 2019) has never been read in the light of the concepts the French philosopher, George Bataille (1897 – 1962) introduced into the world of philosophy and literature even though the enterprise could be abundantly rewarding. Bataille poses the question of general economy as opposed to particular economy. The latter is narrow, rational, self-centered and pivoting around gathering and storage, while the former takes the whole sphere of life into account and concentrates on excess of energy, expenditure, universal wisdom which is far broader and more inclusive, sacrifice and permanence of the sum total of energy available in the living sphere as well as that of the living matter. Oliver, the poet, uses none of the philosopher’s terms, but the scenes she describes in her own poetic style and the language and discourse she uses concerning death reveal the same position and point of view as those of Bataille. That is the gap the present qualitative, library-based study tries to cover at least partially and in particular with regard to the question of death which with the help of an Oliverian stance and in the light of such Bataillean concepts as general economy, excess and expenditure, can turn into a moment of rebirth, vital to the health and a proper functioning of the whole universal system. This two-fold approach will hopefully contribute to both Oliver studies and to the body of research, done on Bataille.